Shock Characteristics of the Opposed Disc Springs (ODS) Shock Isolator with Pretightening under Boundary Friction Condition - An-Min Hui; Ming Yan; Lei Zhang; Ying-Li Jin; Kaiping Wang; Haichao Liu (Shock and Vibration)
In this study, to solve the problems of shock environment and shock isolation, about which there is still a lack of reasonable description, an isokinetic shock distinguishing method (ISDM), which can quantitatively distinguish between shock and forced vibration state, is presented. And the shock isolation performance of an opposed disc springs (ODS) shock isolator with pretightening under boundary friction condition is investigated. The static and dynamic stiffness properties of the ODS shock isolator are discussed. Relying on ISDM, a shock dynamic model of the ODS shock isolator with pretightening under boundary friction condition is established. The average method is adopted to solve the model theoretically. The shock acceleration ratio (SAR), shock displacement ratio (SDR), and relative displacement ratio (RDR) of the model are calculated using the numerical method and verified by experiments. Both numerical and experimental results show that ISDM is effective. And the effects on isolation efficiency of the number of disc springs, additional supporting force, pretightening force, load, and the shock velocity constant of the ODS shock isolator are discussed, which provide guidelines for its further practical application.